Fluid flow in chondritic parent bodies: Deciphering the compositions of planetesimals - Young, E; Ash, R; England, P; Rumble, D (1999)
Alteration of the Allende meteorite caused shifts in oxygen isotope ratios along a single mass fractionation line. If alteration was caused by aqueous fluid, the pattern of oxygen isotope fractionation can be explained only by flow of reactive water down a temperature gradient. Down-temperature flow of aqueous fluid within planetesimals is sufficient to explain the mineralogical and oxygen isotopic diversity among CV, CM, and Cl carbonaceous chondrites and displacement of the terrestrial planets from the primordial slope 1.00 line on the oxygen three-isotope plot.